ATRIAL FIBRILLATION AND FLUTTER IN HYPERTROPHIC CARDIOMYOPATHY - N. S. Krylova; A. E. Demkina; F. M. Khashieva; E. A. Kovalevskaya; N. G. Poteshkina (Российский кардиологический журнал)
Aim. To find out the factors associated with atrial fibrillation/flutter (AF) in patients with hypertrophiccardiomyopathy.Material and methods. Totally 182 HCMP patients included, of those 103 — men (mean age 59,6±14,6y). Diagnosis of AFwas set using ECG or Holter monitoring of ECG using medical charts with the mentioned anamnesis of AF Results. Paroxysmal or permanent form of AF were found in 60 (33%) patients. AF patients were older (64,2±11,2 vs 57,3±15,6 y, p=0,005), with more significant symptomatics(CHFFCbyNYHA2,4±0,8vs2,1±0,8, p=0,02). In AF patients the size of left atrium (LA) was larger than in sinus patients (4,5±0,6 vs 4,1±0,7 cm, p=0,00003). Prevalence of outgoing tract of the left ventricle (OTLV) was nearly same in both groups (50% vs 52,2%, p=0,2), and maximum pressure gradient (PGmax) in OTLV was higher in AF patients (46,0±48,0 vs 21,8±26,6 mmHg, p=0,02). There is and increase of AF with the age (r=0,21, p=0,005), severity of symptoms (r=0,2, p=0,001), LAenlargement(r=0,44, p=0,04), severity of pulmonary hypertension (r=0,47, p=0,004), value of PGmax in OTLV (r=0,23, p=0,02). With the method of binary logistic regression 3 main variables were selected as the most of predictable value for AF: age, LA size, PGmax in OTLV. The model defined that makes to estimate the risk of AF with high diagnostic probability — x 22,0, df=3 (p=0,00006): AF = 0,05307 * age + 0,98065 * LA + 0,01516 * Рймакс in OTLV - 8,66. With the result >0 there is a high risk of AF, and if <0 — the risk of AF is minimum.Conclusion. The model invented for risk prediction in AF in HCMP patients using three predictors: patient age, left atrium diameter and maximum gradient of pressure in OTLV.